Chebyshev-Grüss Type Inequalities for Hadamard \(k\)-Fractional Integrals - Iqbal, Sana; Mubeen, Shahid; Habib, Siddra; Tomar, Muharrem (Communications in Mathematics and Applications, 2018)
Integral inequalities are taken up to be important as they are useful in the study of different classes of differential and integral equations. During the past several years, many researchers have obtained various fractional integral inequalities comprising the different fractional differential and integral operators. A considerable work is done associated with classical and variants of Grüss type inequality, which actually connects the integral of the product of two functions with the product of their integrals. In this paper, we present the Chebyshev-Grüss type inequalities for Hadamard fractional integrals in the framework of parameter \(k > 0\).